(untitled) (Research, Society and Development, 2022)
COVID-19 is a disease caused by the viral agent SARS-CoV-2, which began in 2019 and became a pandemic in 2020. It affected individuals around the world, causing changes since the routine life of populations to serious injuries to those infected. Of these, some require hospitalization in Intensive Care Units due to the severity of the disease. Therefore, in order for the inflammation, hypermetabolism and gastric alterations imposed by the disease to be minimized, it is important to adopt an effective nutritional therapy, which is possible from the identification of the individual at nutritional risk, the establishment of a nutritional diagnosis and the adoption of nutritional therapy. Thus, the objective was to consolidate the data available in the literature on the screening and nutritional assessment tools used in ICUs, as well as the nutritional therapy used in these patients. The methodology was based on the analysis of articles taken from PubMed, SciELO, MedLine and Google Scholar using the Health Sciences Descriptors. Twelve articles that met the criteria were selected. According to the findings in the studies, it is observed that the NRS-2002 is a highly recommended and validated screening tool, as are the subjective global assessment (SGA) and GLIM for nutritional assessment. In addition, it is noted that nutritional therapy follows existing recommendations, but with specificities regarding specific supplements for the disease. In short, the data obtained to date are sufficient for efficient nutritional management, despite the need to develop more studies involving critically ill patients with COVID-19.